Public Policies and Private Savings and Investment in Sub-Saharan Africa : An Empirical Investigation - Ghura, Dhaneshwar (IMF Working Papers; Working Paper ;, 1995)
This paper assesses empirically the role of public policies in stimulating private savings and investment in sub-Saharan African countries, based on data for the period 1986-92. The main findings of the analysis are as follows: (i) policies effective in stimulating private savings and investment include those that keep the rate of inflation low, reduce macroeconomic uncertainty, promote financial deepening, and lower the external debt burden; (ii) measures that promote structural reforms and reduce the budget deficit (without lowering government investment) help to raise private investment; and (iii) declines in government savings are only partially offset by increases in private savings.